ANALISIS FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN MAHASISWA DALAM BERKARIR SEBAGAI AKUNTAN PUBLIK - Firdawati, Ery; Solikah, Mar’atus; Winarko, Sigit Puji (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The purpose of this research is to analyze the effect of professional training, labor market considerations, social values ​​and the work environment on the interest of accounting study program students as public accountants at Nusantara University PGRI. This research was conducted through a quantitative approach using primary data obtained from 63 respondents, namely students from Nusantara University PGRI Kediri, Faculty of Economics and Business, Accounting Study Program. Data analysis techniques in the form of descriptive statistics, classical assumption test, multiple linear regression analysis, determinant coefficient, and hypothesis testing. The results of the study show that professional training has no significant effect on students' interest in choosing careers to become public accountants. Labor market considerations have no significant effect on students' interest in choosing a career as a public accountant. Social value has no significant effect on students' interest in choosing a career to become a public accountant. The work environment has a significant effect on students' interest in choosing a career to become a public accountant. Based on the results of simultaneous testing, it is known that there is a significant influence between the variables of professional training, labor market considerations, social values ​​and the work environment with students' interest in choosing a career as a public accountant.